Migration and Farmland Abandonment in Nepal: A Systematic - Tiwari, Pradip Raj (Asian Journal of Population Sciences, 2025)
This systematic review aims to synthesize current knowledge on farmland abandonment in Nepal through the lens of migration. Specifically, it addresses the question: How does the existing literature on farmland abandonment incorporate migration issues in Nepal? By exploring this question, the review contributes to the broader discourse on the effects of migration on farmland abandonment, offering insights that can inform policy and research on land use and rural development in Nepal. The relationship between farmland abandonment and migration in Nepal is complex and multifaceted, driven by economic, social, cultural, environmental, and policy-related factors. The reviewed articles focused more on drivers of farmland abandonment and migration and treated the drivers rather than their cause-effect relationship on farmland abandonment. So, farmland abandonment research needs to focus on migration issues to gain a comprehensive understanding of the issues. By understanding these relations, stakeholders can develop integrated strategies to address migration and farmland abandonment, ensuring sustainable rural development in Nepal.